ACE inhibition for severe bronchopulmonary dysplasia – an approach based on physiology. Issue 17 (5th September 2018) - Sehgal, Arvind; Krishnamurthy, Mohan B.; Clark, Megan; Menahem, Samuel
Abstract: Premature infants have a high incidence of bronchopulmonary dysplasia (BPD). Systemic hypertension, arterial thickness and stiffness, and increased systemic afterload may all contribute to BPD pathophysiology by altering left ventricular (LV) function and increasing pulmonary venous congestion by lowering end‐diastolic compliance. This case series studied the usefulness of angiotensin‐converting enzyme (ACE) inhibition by measuring clinical and echocardiographic improvements in six consecutive infants with "severe" BPD unresponsive to conventional therapy. The range of gestation and birthweight were 23–29 weeks and 505–814 g, respectively. All required mechanical ventilation (including high‐frequency oscillation) and all but one were administered postnatal corticosteroids. Other treatments including sildenafil and diuretics made no clinical improvements. Captopril was started for systemic hypertension after cardiac and vascular ultrasounds which were repeated 5 weeks later. A significant reduction in oxygen (55 ± 25 to 29 ± 3%, two‐tailed P  = 0.03) and ventilator requirements, and improved cardiovascular parameters were noted. This included a trend toward reduction in aorta intima media thickness [840 ± 94 to 740 ± 83  μ m, P  = 0.07] and an increased pulsatile diameter [36 ± 14 to 63 ± 25  μ m, P  = 0.04]). Improvements were observed for both systolic (increased LV output, 188 ± 13 to 208 ± 13 mL/kg/min, P  = 0.046 and mean velocity of circumferential fiber shortening, 1.6 ± 0.2 to 2.5 ± 0.3 [circ/sec], P  = 0.0004) and diastolic (decreased isovolumic relaxation time, 69.6 ± 8.2 to 59.4 ± 5 msec, P  = 0.044) function which was accompanied by increased pulmonary vein flow. Right ventricular output increased accompanied by a significant lowering of pulmonary vascular resistance. These findings suggest that improving respiratory and cardiac indices (especially diastolic function) warrants further exploration of ACE inhibition in BPD infants unresponsive to conventional therapy. Abstract : While bronchopulmonary dysplasia is the most common respiratory sequelae of preterm birth, contribution of systemic arterial thickness/stiffness to its pathophysiology is not well appreciated. This article demonstrates the usefulness of systemic afterload reduction using an angiotensin‐converting enzyme inhibitor (ACE, captopril) in a cohort of infants with "severe" BPD, unresponsive to standard therapy. The role of ACE inhibitors beyond the reduction in blood pressure is discussed.